Design and Construction of a 1.2KVA Carbon-Free and Fueless (CFF) Generator - Ibanagum, Julius Okechukwu; Okoye, Kelechi R.E. (Journal of Research in Industrial Technology and Educational Studies, 2025)
There have been problems with public power generation and distribution in Nigeria, and this has affected many Nigerians in one way or the other. Similarly, apart from health hazards, many deaths have been recorded as a result of use of diesel or fuel dependent generators, Additionally, the production of electrical power via solar energy is increasingly gaining more awareness, but the cost of its installation in residential buildings is not affordable by an average Nigeria. Hence, the need to design and construct a more environmental-friendly and less expensive generator for average Nigerians. This study therefore adds to electrical power generation to design and construct a 1.2KVA Carbon Free Fueless (CFF) generator. The study employed an experimental design approach following designs procedures for constructing generator. The construction employed some resources such as alternator, bridge rectifier, capacitor, stator winding. Having constructed the CFF generator with an external solar power source, it shows that its performance evaluation is 1,200W (1.2KVA) CFF-generating set with a minimum time of six hours.
Keywords: Carbon free; fuel-less; generator; electrical energy; renewable energy; power generation